Human-machine symbiosis: ambivalent intuitions regarding gain and loss of personal control explain acceptance of smart mobility aids - Löloff, Johanna; Theisen, Maximilian; Mertens, Alica; Funke, Joachim (Behaviour & information technology, 2024)
Smart mobility aids invoke conflicting impressions of enhanced mobility and being restricted and dependent. This ambivalence between perceived gain and loss of personal control might affect the acceptance of these devices. In a preregistered study (N = 194), we investigated people’s expectations on how using a flexible exosuit and a rigid exoskeleton would affect their personal control and tested how this influenced their acceptance of those devices. Overall, participants anticipated a net gain of personal control by using smart mobility aids. There was no difference in anticipations of gain of control between devices, but anticipations of loss of control were higher for the rigid exoskeleton than for the flexible exosuit. Anticipated gain and loss of control explained more than 50% of the variance in the acceptance of the investigated devices. The belief that a smart mobility aid would increase the user’s personal control was more predictive of overall acceptance than the belief that such a device would limit the user’s personal control. Overall, the current findings reveal that potential users’ expectations regarding changes in personal control, in particular the degree to which positive changes are expected, are a key determinant of acceptance of smart mobility aids.
Online veröffentlich: 2. November 2023
Gesehen am 08.01.2024